2017
DOI: 10.4103/jmp.jmp_89_17
|View full text |Cite
|
Sign up to set email alerts
|

Estimating second malignancy risk in intensity-modulated radiotherapy and volumetric-modulated arc therapy using a mechanistic radiobiological model in radiotherapy for carcinoma of left breast

Abstract: Objectives:The aim of this study is to estimate second cancer risk (SCR) in intensity-modulated radiotherapy (IMRT) and volumetric-modulated arc therapy (VMAT) using a mechanistic radiobiological model. The model also takes into account patient age at exposure and the gender-specific correction factors of SCR.Materials and Methods:Fifty IMRT and VMAT plans were selected for the study. Monte Carlo-based dose calculation engine was used for dose calculation. Appropriate model parameters were taken from the liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Our results compare very favorably with data from the literature. Fogliata et al, as well as Sakthivel et al showed a lower risk for second malignancy following t-IMRT as compared to t-VMAT [31, 39]. In our study, EAR was calculated exclusively using the full model described by Schneider et al, which best takes into account tissue and dose-dependent cell biological properties such as cell destruction and cell regeneration.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our results compare very favorably with data from the literature. Fogliata et al, as well as Sakthivel et al showed a lower risk for second malignancy following t-IMRT as compared to t-VMAT [31, 39]. In our study, EAR was calculated exclusively using the full model described by Schneider et al, which best takes into account tissue and dose-dependent cell biological properties such as cell destruction and cell regeneration.…”
Section: Discussionmentioning
confidence: 98%
“…Sakthivel et al evaluated the relationship between number of MUs and EAR. According to their results, however, no strong relationship between the two parameters was seen [39].…”
Section: Discussionmentioning
confidence: 99%
“…[ 31 32 ] Many studies have suggested that radiobiological modeling that can instantly represent local tumor control and normal tissue complications is a key factor in choosing the optimal radiotherapy technique. [ 33 34 35 ]…”
Section: Discussionmentioning
confidence: 99%
“…Many literatures have reported that leakage radiation would contribute to the integral dose to peripheral normal tissue. This may lead to increased risk of secondary malignancy (Sakthivel et al, 2017).…”
Section: Discussionmentioning
confidence: 99%